Analisis Struktur Aktiva, Beban Pajak dan Struktur Keuangan pada Sektor Industri Tekstil dan Garmen yang Go Publik di Bursa Efek Indonesia - Sukriyanto Pakaya (Fakultas Ekonomi, Universitas Ichsan Gorontalo, 2020)
Structure of asset is determination of how much allocation for each component asset, either in current assets or in fixed assets. Tax expense is sum combined current and deferred taxes that are taken into account in determining the profit and loss for a period. Financial structure is way companies finance their assets. This study aims to know and analyze structure of assets, tax burden and financial structure in textile and garment industry sector Go Public in Indonesia Stock Exchange. Results showed that textile and garment industry sector has a high asset structure and tax burden.This high asset structure is seen in high fixed assets in this sector, so that is used as collateral for corporate debt. The high tax burden on this industry, greater profit from use of debt. Financial structure of this industry very high, because with use of debt as a very large capital, so risky for investors.